The contributions to long-term health-relevant particulate matter at the UK EMEP supersites between 2010 and 2013: Quantifying the mitigation challenge. (October 2016) - Malley, Christopher S.; Heal, Mathew R.; Braban, Christine F.; Kentisbeer, John; Leeson, Sarah R.; Malcolm, Heath; Lingard, Justin J.N.; Ritchie, Stuart; Maggs, Richard; Beccaceci, Sonya; Quincey, Paul; Brown, Richard J.C.; et al.
Abstract: Human health burdens associated with long-term exposure to particulate matter (PM) are substantial. The metrics currently recommended by the World Health Organization for quantification of long-term health-relevant PM are the annual average PM10 and PM2.5 mass concentrations, with no low concentration threshold. However, within an annual average, there is substantial variation in the composition of PM associated with different sources. To inform effective mitigation strategies, therefore, it is necessary to quantify the conditions that contribute to annual average PM10 and PM2.5 (rather than just short-term episodic concentrations). PM10, PM2.5, and speciated water-soluble inorganic, carbonaceous, heavy metal and polycyclic aromatic hydrocarbon components are concurrently measured at the two UK European Monitoring and Evaluation Programme (EMEP) 'supersites' at Harwell (SE England) and Auchencorth Moss (SE Scotland). In this work, statistical analyses of these measurements are integrated with air-mass back trajectory data to characterise the 'chemical climate' associated with the long-term health-relevant PM metrics at these sites. Specifically, the contributions from different PM concentrations, months, components and geographic regions are detailed. The analyses at these sites provide policy-relevant conclusions on mitigation of (i) long-term health-relevant PM in the spatial domain for which these sites are representative, and (ii) the contribution of regional background PM to long-term health-relevant PM. At Harwell the mean (± 1 sd) 2010–2013 annual average concentrations were PM10 = 16.4 ± 1.4 μg m − 3 and PM2.5 = 11.9 ± 1.1 μg m − 3 and at Auchencorth PM10 = 7.4 ± 0.4 μg m − 3 and PM2.5 = 4.1 ± 0.2 μg m − 3 . The chemical climate state at each site showed that frequent, moderate hourly PM10 and PM2.5 concentrations (defined as approximately 5–15 μg m − 3 for PM10 and PM2.5 at Harwell and 5–10 μg m − 3 for PM10 at Auchencorth) determined the magnitude of annual average PM10 and PM2.5 to a greater extent than the relatively infrequent high, episodic PM10 and PM2.5 concentrations. These moderate PM10 and PM2.5 concentrations were derived across the range of chemical components, seasons and air-mass pathways, in contrast to the highest PM concentrations which tended to associate with specific conditions. For example, the largest contribution to moderate PM10 and PM2.5 concentrations – the secondary inorganic aerosol components, specifically NO3 − – were accumulated during the arrival of trajectories traversing the spectrum of marine, UK, and continental Europe areas. Mitigation of the long-term health-relevant PM impact in the regions characterised by these two sites requires multilateral action, across species (and hence source sectors), both nationally and internationally; there is no dominant determinant of the long-term PM metrics to target. Highlights: PM and PM component measurements at UK EMEP supersites (2010 − 2013) were analysed. Analysis focussed on conditions producing long-term health-relevant PM (annual average concentrations). Moderate PM concentrations made largest contribution to long-term health-relevant PM. Moderate PM concentrations were produced across range of components, months and air mass pathways. There was no single, key determinant of long-term health-relevant PM at these sites.